Factors Affecting The Completeness Of Completeness Of Basic Immunization Of Infants Aged 12 To 24 Months In The Working Area Of Puskesmas X Pekanbaru City - Aridiansyah Aridiansyah; Quenda Anisa; Supriadi Supriadi (International Journal of Public Health, 2024)
Background: Complete Basic Immunization (IDL) is an indicator in the immunization program. IDL aims to actively gain early immunity. IDL data at Puskesmas X in 2021 was 83.5% and there was a decrease in the percentage rate in 2022 to 82.87%. Based on an initial survey, on May 9-19, 2023, it was found that out of 73 mothers who brought their children to the posyandu for immunization, around 22 children (30%) were not fully immunized. Objective: Knowing the factors that influence the completeness of immunization in the working area of Puskesmas X Pekanbaru City. Methods: Using analytic observational study design, with cross sectional research design. This research was conducted at Puskesmas X Pekanbaru city. The sampling technique was done by accidental sampling. Variables of knowledge level, and education were analyzed using Kendall Tau test, while variables of employment, family support, mother's attitude and number of children used contingency coefficient test. Results: The results of the Kendall Tau test analysis of the variable level of knowledge, and education obtained a p value of 0.001 and 0.392 respectively. While in the contingency coefficient test the variables of employment, family support, maternal attitudes and number of children obtained a p value of 0.889; 0.000; 0.000 and 0.455 respectively. Conclusion: There is a significant relationship between the level of knowledge, mother's attitude and family support with the completeness of basic immunization of infants aged 12-24 months in the working area of Puskesmas X Pekanbaru City.